Analysis of Gray Matter Volume (GMV) and White Matter Hyperintensity (WMH) in Ischemic Stroke Patients with Fluid Attenuated Inversion Recovery (FLAIR) Imaging - Ade Lina Nur Fadlilah; Johan Andoyo Effendi Noor; Yuyun Yueniwati; Karimah (Postgraduate, University of Mataram, 2023)
Stroke is a serious health problem faced by almost all over the world. The occurrence of ischemic stroke could affect the gray matter volume (GMV) in the human brain. In Magnetic Resonance imaging of an ischemic stroke with a FLAIR sequence, a white lesion known as the white matter hyperintensity (WMH) is often found. We studied correlation between gray matter volume (GMV) and white matter hyperintensity (WMH) in ischemic stroke patients using fluid attenuated inversion recovery (FLAIR) sequences. The MRI data were taken randomly from ten ischemic stroke patients (mean age 46.9 years) and ten normal patients (mean age 36.8 years). FLAIR axial image parameters, i.e. TE (time echo), TR (time repetition), and TI (time inversion) were analyzed. The results reveal that the TE and TR values in FLAIR images of normal and ischemic stroke patients are classified as long TE (more than 70 ms), long TRÂ (more than 1500 ms) and long TI (more than 1700 ms). The mean GMV of ischemic stroke patients (1.371 cm3) is smaller than the GMV of normal patients (2.267 cm3). This is related to the presence of white matter hyperintensity (WMH) in ischemic stroke patients